A Constitutional Study on the Protection of Indian Labour Laws and Social Security: Examining the Impact of Globalization on Indian Labor Laws and Social Security (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India like some other country of the world couldn't manage the cost of itself to stay outside the grip of effect of globalization on its economy and mechanical relations. In this financial request, common laborers are primarily tasked with dismissing this crucial section of the general public because no framework can work easily. Globalization has an impact on legislation on employment and public disability. The employer's stability of the modern worker is at risk during globalisation, due to the inclination of the company towards contract work. In 1999 the National Labor Commission was chosen to reflect on the impact on Indian employment laws of globalisation, and in 2002 its report was presented with recommendations to modify existing labor laws. Several efforts have been made to provide security for workers of the global dimension, such as the ILO, the International Association of Social Security and the Social Security Alumni Association etc. Numerous insurance and welfare conventions have been fulfilled by ILO. The Universal Declaration of Human Rights, 1948, International Convention on Human Rights, 1966, contains rules on acquisition. The Preamble to India's Constitution guarantees its subjects equity and security. However, the Constitution of India does not accommodate the country's endless supply by establishing government-run savings for all nevertheless, it explicitly considers its Directive Principles of State Policy in Part I V to address the subject. Government managed savings to the laborers in the sorted out Sector is given through five Focal Acts, to be specific, the1923,Employees‟the Industrial Disputes Act,1947, the Employees State Insurance Act,1948 the Employees Provident Funds and Miscellaneous Provisions Act,1952, the Maternity Benefit Act,1961 and the Payment of Gratuity Act,1972. The Government has sanctioned certain enactments for the insurance of disorderly laborers. A portion of the enactments relevant to the specialists incorporate the Beedi Workers Welfare Fund Act, 1976, the Building and Other Construction Workers (RECS) Act, 1996 and the Building and Other Construction Workers Welfare Cess Act, 1996, the Unorganized Sector Workers Social Security Act, 2008 and so on.